The Effect of Different Synthesis Solvents and Dialysis Processes on the Optical Properties of Carbon Dots from Spent Coffee Grounds using the Solvotermal Method - Putri, Wahyuni Eka; Sjahriza, Ahmad; Sugiarti, Sri (Departemen Kimia, 2025)
The distinctive optical properties of carbon dot (CD) make CD is one of the most widely developed carbon nanomaterials today. CD can be synthesized from materials that high in carbon content, such as spent coffee grounds. The optical properties of synthesized CD are influenced by several factors, including the solvent used to synthesize it and the purification method. The purification process that can be done is dialysis. However, this technique is not always used in several researches to purify CD. This study aims to synthesize CD from spent coffee grounds through solvothermal methods with three different solvents, which are water, 50% ethanol (v/v), and absolute ethanol that purified by dialysis and without dialysis and to characterize the differences in its optical properties. The results showed that CD was successfully synthesized with these three solvents, but the optical properties were different. All three solvents produce CD that emits blue light, but differ in intensity. The addition of ethanol can double the luminescence intensity of CD and CD synthesized with 50% ethanol produce the highest luminescence intensity. In addition, CD purified without dialysis produce twice as high luminescence intensity as CD purified by dialysis.